2017
DOI: 10.21608/ejchem.2017.1509.1110
|View full text |Cite
|
Sign up to set email alerts
|

Fire Performance of Poly Propylene Treated With Ammonium Polyphosphate and Kaolin

Abstract: IntroduetionPolypropylene (PP) is one of the popular members of thermoplastic polymers which are widely used in various applications due to their interesting mechanical properties. However, its low thermal stability and high flammability hazard attributed to restriction in its use in other industrial applications [1]. Hence, flame retardant additives have to incorporate in polymer matrix improving their flame retardancy and enhancing their thermal stability such as phosphate-nitrogen materials and aluminosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In our previous studies [20][21][22], the MMt clay and the ammonium polyphosphate were used as flame retardants for polypropylene (PP). It was found that adding 10% of ammonium polyphosphate to PP could improve its thermal stability and the flame retardancy without considerable effects on the mechanical properties of the PP.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [20][21][22], the MMt clay and the ammonium polyphosphate were used as flame retardants for polypropylene (PP). It was found that adding 10% of ammonium polyphosphate to PP could improve its thermal stability and the flame retardancy without considerable effects on the mechanical properties of the PP.…”
Section: Introductionmentioning
confidence: 99%